Exploring Universal Moral Values in Animation Movie: A Case in Inside Out Movie by Pete Docter - Sjamsuddin, Meilia; Said, Mashadi (Advances in Social Sciences Research Journal, 2024)
The purpose of this study is to explore the universal moral values as portrayed in Inside Out movie by Pete Docter. This study was conducted using a qualitative method as its approach. The data were collected from the dialogues in the Inside Out movie using content analysis to elicit the universal moral values as portrayed in the movie, Inside Out. The data were analyed using Kinnier, Kernes, and Dautheribes to determine the boundaries of the study.The results of the analysis show that the universal moral values as portrayed in Inside Out movie are devided into four categories, i.e. commitment to something greater than oneself; self-respect but humility, self-discipline, and acceptance of personal responsibility; respect and caring for others; and caring for other living things and the environment.